Efficacy of a Novel Bioactive Glass-Polymer Composite for Enamel Remineralization following Erosive Challenge - Farnoosh Fallahzadeh; Soolmaz Heidari; Farhood Najafi; Maryam Hajihasani; Nooshin Noshiri; Neda F. Nazari (International Journal of Dentistry)
Introduction. Dental caries is the most common cause of tooth loss. However, it can be stopped by enhancing remineralization. Fluoride and casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) are among the most important remineralizing agents. Recent studies have used bioactive glass as a remineralizing agent in different forms. This study aimed to assess the efficacy of a composite paste (prepared by mixing urethane polypropylene glycol oligomer with bioactive glass powder for easier application). Materials and Methods. Enamel disks were cut out of the buccal surface of extracted sound third molars. The samples were randomly divided into 3 groups of 15 and underwent Vickers microhardness test. X-ray diffraction (XRD) and field emission scanning electron microscopy/energy dispersive X-ray spectroscopy (FESEM/EDS) were performed. All samples were immersed in a demineralizing solution for 14 days. The tests were then repeated. Next, bioactive glass paste, fluoride, and CPP-ACP were applied on the surface of the samples and they were then stored in an artificial saliva for 14 days. The tests were repeated again. The microhardness values were analyzed using repeated measures ANOVA followed by one-way ANOVA and Tukey’s post hoc test (P<0.05). Results. The microhardness of the bioactive glass group was significantly higher than that of other groups (P<0.05). XRD revealed an enamel structure more similar to sound enamel in the bioactive glass and CPP-ACP groups compared with the fluoride group. FESEM/EDS revealed higher hydroxyapatite deposition in the bioactive glass group than in the other two groups. Conclusions. All three remineralizing agents caused remineralization, but bioactive glass paste had a greater efficacy.